Hak Atas Tanah sebagai Permukiman Penduduk di Daerah Aliran Sungai Kota Tanjungbalai - Perdana, Indra; Siregar, Fazriana; Hutama Hutabarat, Dany Try (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The riverbank area is an inseparable part of the water resources management area which cannot be owned and/or controlled by individuals, community groups, or business entities. Tanjungbalai City As a city flanked by 2 major rivers, namely the Silau river which empties into the Asahan river as a city that has many rivers. does not rule out the possibility to make the watershed as a place to live by the people of the city of Tanjungbalai. The purpose of this study is to see the response of the people of Tanjungbalai city who use the watershed as a place to live (housing) and the policies made by the local government to the events that occur. The method used in this study is the empirical juridical method and the observation technique is carried out by using the interview method and analyzing the results of the questionnaire on 35 (thirty five) households who choose the watershed as a place to live. The results in this study are people who live in the watershed due to middle to lower economic factors, as well as the lack of supervision from the local government. And there is no Tanjungbalai City Government Policy on housing and settlements that prohibits building housing in places that are at risk of causing danger.